2-Acetyl-1-pyrroline: A key aroma component of aromatic rice and other food products. Issue 6 (18th August 2018) - Routray, Winny; Rayaguru, Kalpana
ABSTRACT: 2-Acetyl-1-pyrroline is an aroma compound that gives aromatic rice its characteristic flavor. This compound either is present naturally in various food sources or is generated during certain processing methods, as reported in a number of studies. This review focuses on several sources of 2-acetyl-1-pyrroline, including aromatic rice, and the factors, including chemical and genetic parameters, affecting the formation of 2-acetyl-1-pyrroline. Extensive work has been conducted on the agricultural parameters, postharvest processing, storage, and cooking methods, influencing the concentrations of 2-acetyl-1-pyrroline in different food commodities. This article is an attempt to emphasize the importance of this compound in the food industry as a major aroma compound.